2018
DOI: 10.4155/fmc-2017-0241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Sodium-Glucose Transporter 2 Inhibitors as Potential Antidiabetic Agents

Abstract: SGLT2 inhibitors were promising and novel antidiabetic drugs which suppressed glucose reabsorption and increased urinary glucose exertion. This review paper are aimed to summarize the recent progress of SGLT2 inhibitors during the last 5 years. This paper first summarizes the information of SGLT2 inhibitors, including mechanism, evolution and then focuses on the recent efforts on structure-activity relationships and structural optimization of SGLT2 inhibitors. Finally, the corresponding clinical therapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Humans with a SGLT1-inactivating mutation experience glucose malabsorption with diarrhea, dehydration, and minimal glucosuria. In contrast, individuals with a SLGT2-inactivating mutation have pronounced renal glucosuria but are otherwise healthy. SGLT inhibitors have had significant impact for the treatment diabetes. SGLT2-selective inhibitors are preferred due to their ability to lower blood sugar with selectivity for kidney reabsorption. Currently, there are several SGLT2 inhibitors on the market that include 61 (dapagliflozin), 63 (canagliflozin), 64 (ipragliflozin), 65 (empagliflozin), and 67 (luseogliflozin) for T2DM (Figure ).…”
Section: Metabolism Targetsmentioning
confidence: 99%
“…Humans with a SGLT1-inactivating mutation experience glucose malabsorption with diarrhea, dehydration, and minimal glucosuria. In contrast, individuals with a SLGT2-inactivating mutation have pronounced renal glucosuria but are otherwise healthy. SGLT inhibitors have had significant impact for the treatment diabetes. SGLT2-selective inhibitors are preferred due to their ability to lower blood sugar with selectivity for kidney reabsorption. Currently, there are several SGLT2 inhibitors on the market that include 61 (dapagliflozin), 63 (canagliflozin), 64 (ipragliflozin), 65 (empagliflozin), and 67 (luseogliflozin) for T2DM (Figure ).…”
Section: Metabolism Targetsmentioning
confidence: 99%
“…Extending our earlier efforts in the area of nanocatalysis [ 5 , 6 , 7 ], in this article La 2 O 3 nanoparticles immobilized onto the chitosan matrix were prepared ( Figure 1 ) and then employed as a promising heterogeneous basic catalyst to synthesis pyridines and pyrazoles. These azines and azoles have privileged antitumor [ 12 , 13 , 14 , 15 ], antidiabetes [ 16 ], antimicrobial [ 17 , 18 ], anti-HCV [ 14 , 19 , 20 ], and antidepressant [ 21 , 22 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2 inhibitors reduce blood glucose via inhibiting the reabsorption of glucose by the proximal renal tubules, resulting in osmotic diuresis and glycosuria, and its mechanism of action is insulin-independent. [ 6 , 7 ] However, one of the adverse reactions of SGLT2 inhibitors is an increase in LDL-C and HDL-C levels, which may increase the risk of cardiovascular disease. EMPA-REG OUTCOME ClinicalTrial [ 8 , 9 ] has shown that empagliflozin, used to treat type 2 diabetes mellitus, was associated with a mild increase in LDL-C and HDL-C in patients.…”
Section: Introductionmentioning
confidence: 99%